Comparative analysis of reconfigurable patch antenna array for different liquid crystal substrates - Chandra S.; Dwivedi S. (My University, 2025)
This paper presents the frequency reconfigurable patch antenna array based on tunable liquid crystal and the comparison of tuning range with four liquid crystal (LC) substrates namely BL037, BL006, E7 and GT3-24002. Both the conventional and reconfigurable antennas are designed to operate at 2.45 GHz frequency. The proposed structure satisfies tuning range of 1.70%, 2.56%, 2.28% and 4.09% for LC material BL037, BL006, E7 and GT3-24002 respectively. Using Liquid crystals we can cover several frequency bands and overcome the problem of narrow band antenna .The designed antenna has various applications in S band. The antenna design and simulation is done with the help of HFSS software. © 2019 URSI. All rights reserved.